2008
DOI: 10.1211/jpp.60.4.0005
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of antibiotics on ciliary beat frequency of human nasal epithelial cells exposed to bacterial toxins

Abstract: In the present study, we explored whether the cilio-inhibitory effect induced by toxins derived from bacterial infections could be compensated for by a cilio-stimulatory effect of antibiotics. Human nasal epithelial cells (HNEC) expressing beating cilia were grown as monolayers. Ciliary beat frequency (CBF) was determined using an inverted microscope coupled with a high-speed digital camera. Clarithromycin and neomycin did not influence ciliary activity. Bacitracin, clindamycin, gramicidin and roxithromycin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
4
15
0
Order By: Relevance
“…Despite this, in the current study S. epidermidis biofilm was associated with similar degrees of epithelial damage and fungal biofilm formation as the other species. In addition to cilial destruction, it is known that bacterial toxins from S. aureus and P. aeruginosa are capable of significantly impeding cilia beat frequency, an additional factor which may promote both bacterial and fungal biofilm formation.…”
Section: Discussionsupporting
confidence: 92%
“…Despite this, in the current study S. epidermidis biofilm was associated with similar degrees of epithelial damage and fungal biofilm formation as the other species. In addition to cilial destruction, it is known that bacterial toxins from S. aureus and P. aeruginosa are capable of significantly impeding cilia beat frequency, an additional factor which may promote both bacterial and fungal biofilm formation.…”
Section: Discussionsupporting
confidence: 92%
“…Ciliary beat frequency can be reduced after exposure to PA [20, 21], potentially mediated by virulence factors such as pyocyanin [22] and rhamnolipids [23]. Previous studies have demonstrated that mucus production, composition, and rheology could be affected by PA [24] and pyocyanin in particular is associated with goblet cell hyperplasia and mucus hypersecretion [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to exhibiting primary antimicrobial activity, macrolides have been shown to have immunomodulatory effects (38) and stimulate ciliary beat frequency, consequently improving mucociliary clearance (39,40). However, of the many effects of macrolides, stimulation of ciliary beat frequency is not expected in patients with Kartagener's syndrome with ciliary dyskinesia.…”
Section: Discussionmentioning
confidence: 99%